MEDIA VIDEO POWTOON UNTUK MENINGKATKAN HASIL BELAJAR IPA SD MATERI PERKEMBANGBIAKAN VEGETATIF TUMBUHAN - Binti Muakhirin (PROGRAM STUDI PENELITIAN DAN EVALUASI PENDIDIKAN, 2022)
This study aims to determine the effectiveness of the use of Powtoon video learning media in an effort to improve science learning outcomes at SDN Cibuk Lor Seyegan, Sleman Yogyakarta in class VI students in the 2020/2021 academic year. This research used Classroom Action Research method with 2 cycles with 2 meetings in each cycle. The data collection instrument used an observation sheet on the implementation of learning and tests to determine the improvement of student learning outcomes. The results showed that the mastery of learning from cycle 1 to cycle 2 reached 75%. In addition, student learning outcomes also increased with the acquisition of test results from an average of 67.65 to 74.12. The use of powtoon video learning media can improve student learning outcomes at SD Negeri Cibuk Lor on plant vegetative propagation materials.